Management of left ventricular thrombus: a narrative review - Cruz Rodriguez, Jose B. (Ann Transl Med, 2021)
Left ventricular thrombus (LVT) is a serious complication of acute myocardial infarction (MI) and also non-ischemic cardiomyopathies. We performed a narrative literature review, manual-search of reference lists of included articles and relevant reviews. Our literature review indicates that the incidence of LVT following acute MI has decreased, probably due to improvement in patient care as a result of better and earlier reperfusion techniques. Predictors of LVT include anterior MI, involvement of left ventricular (LV) apex (regardless of the coronary territory affected), LV akinesis or dyskinesis, reduced LV ejection fraction (LVEF), severe diastolic dysfunction and large infarct size. LVT is associated with increased risk of systemic embolism, stroke, cardiovascular events and death, and there is evidence that anticoagulant therapy for at least 3 months can reduce the risk of these events. Cardiac magnetic resonance (CMR) has the highest diagnostic accuracy for LVT, followed by echocardiography with the use of echocardiographic contrast agents (ECAs). Although current guidelines suggest use of vitamin K antagonist (VKA) for a minimum of 3 to 6 months, there is growing evidence of the benefits of direct acting oral anticoagulants in treatment of LVT. Embolic events appear to occur even after resolution of LVT suggesting that anticoagulant therapy needs to be considered for a longer period in some cases. Recommendations for the use of triple therapy in the presence of the LVT are mostly based on extrapolation from outcome data in patients with atrial fibrillation (AF) and MI. We conclude that the presence of LVT is more likely in patients with anterior ST-segment elevation MI (STEMI) (involving the apex) and reduced ejection fraction (EF). LVT should be considered a marker of increased long-term thrombotic risk that may persist even after thrombus resolution. Ongoing clinical trials are expected to elucidate the best management strategies for patients with LVT.